Comprensión lectora y rendimiento escolar en el área de ciencias sociales en estudiantes del cuarto grado de secundaria en la Institución Educativa Padre Severino Deshaies del distrito de Fernando Lores 2021 - Macedo Huayunga, Juan Luis (2022)
To determine the relationship between reading comprehension and school performance in the area of social sciences in students of the fourth grade of secondary education of the Educational Institution "Padre Severino Deshaies" located in the district of Fernando Lores, during the 2021 school year; It has been the main objective of the investigation, as a result of the results obtained, the following conclusions were reached: It can be concluded that reading comprehension and school performance, according to the students' appreciation, have a High level in the field of their school development, in which 67.5% show High Performance and 32. 5% an Average Yield. Evidently, there is a highly significant statistical relationship between the Reading Comprehension variable and the School Performance variable. The dimensions of reading comprehension: literal comprehension, inferential comprehension and critical comprehension; show the following result: (r=0.632**; r=0.476**, r=0.630**, 0.502** V Sig. < 0.01). This reveals the existence of a significant statistical relationship between reading comprehension and performance school and it can be affirmed that what is mentioned in the general hypothesis is fulfilled. Consequently, the reading comprehension in the students of the fourth grade of secondary education of the Educational Institution of the rural area "Padre Severino Deshaies" located in the district of Fernando Lores, province of Maynas in the Loreto region, during the school year 2021, has its main strength in the literal comprehension style, and should strengthen the inferential and critical style.